Distortions for Nothing - Optimal Taxation of (Un)Distributed Profits - Etienne Lehmann; Eddy Zanoutene (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
We study the optimal taxation of corporate and dividend income when entrepreneurs can use retained earnings to reduce their tax burden. We show that eliminating dividend taxes while increasing the corporate income tax (CIT) to keep investment unchanged raises total tax revenue. Our simulations suggest net revenue gains of 0.1-0.4% of GDP. In an infinite-horizon model, the optimal policy sets dividend taxes to zero in every period. As the discount factor approaches one and when the planner values only workers' welfare, the optimal steady-state CIT converges to a standard inverse elasticity rule.
Keywords: H21; H24; H25; H26; H32; 330; corporate tax; dividend tax; optimal taxation; capital taxation